Lights and Shadows of Economic Restructuring: Reform Experience Through the Lens of a Kharkiv Enterprise - Chornyi , Dmytro (V. N. Karazin Kharkiv National University Bulletin History of Ukraine. Ukrainian Studies: Historical and Philosophical Sciences, 2025)
Purpose. The article examines the course of economic restructuring from 1985 to 1990 through the lens of one of Kharkiv’s largest enterprises of that time, the Kharkiv Electromechanical Plant, and to determine to what extent external factors versus internal plant factors caused difficulties in the reform process and the accumulation of unresolved problems. Methods. The research is based on the analysis of public speeches by individuals directly involved in production and management processes, using microhistorical approaches to studying narrative documents, statistical materials stored in the DAHO, as well as the plant’s korporative newspaper from 1986 to 1990. Results. The research results show that the implementation of economic reforms during the restructuring period was and remains one of the most acute and controversial chapters in our history. The analysis of the documents indicates that the failures of the enterprise were largely due to external factors: the policies of the relevant ministry, and the lack of a program of action at the national level. Among the internal factors, attempts by the management to operate within the familiar framework, particularly by agreeing to the imposed "rules of the game" and hoping to achieve success through lobbying, had a negative impact. At the same time, a significant portion of the workers was constructively inclined and actively participated in the process until 1989 but gradually lost motivation. Conclusions. The history of KHEMZ shows that it was not the severing of existing ties, but rather the persistent imposition of old ineffective connections on the enterprise that undermined reform efforts since 1986. The dictatorship of the Moscow ministry and resistance to the collective’s aspirations characterize the mentality of the representatives of the union center, especially regarding the transition to lease, preference for enterprises outside Ukraine, and the imposition of top-down requirements to simultaneously increase production and carry out deep reconstruction. In the future, it is worth involving oral history methods to study the history of the industry in the late 1980s – early 1990s.